Development of an Assessment Instrument Based on Wiggins and McTighe’s Six Facets of Understanding for Chemical Equilibrium - Dwiraga, Legia Ladjesta; Holiwarni, Betty; Wulandari, Putri Adita (Journal of The Indonesian Society of Integrated Chemistry, 2025)
This study aimed to develop an assessment instrument grounded in Wiggins and McTighe’s Six Facets of Understanding and to examine its feasibility through expert validation and classical item analysis. The study employed a research and development (R&D) approach using the ADDIE model (Analyze, Design, Develop, Implement, Evaluate). The development process in this study was conducted up to the Development stage. Expert validation (three validators) indicated that the instrument was highly valid in terms of construction (94%) and achieved perfect validity for content/material and language aspects (100%). A small-group trial also showed positive user responses, with high readability (91%) and adequate time allocation (74%). Teachers’ responses indicated very high ratings for relevance/fit (100%), language clarity (87.5%), and usefulness (95.83%). Item analysis showed that all 10 items were valid, and the instrument demonstrated high reliability (Cronbach’s alpha = 0.846). The difficulty indices were moderate, and most items showed acceptable-to-good discrimination. Overall, the developed instrument is feasible to proceed to the Implementation stage in future research. Keywords:       alternative assessment; learning outcomes; Merdeka Curriculum (Independent Curriculum); chemical equilibrium.